2015
DOI: 10.1021/acs.jafc.5b03873
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Characterization of Hot Pepper (Capsicum annuum “CM334”) during Fruit Development

Abstract: Non-targeted metabolomic analysis of hot pepper (Capsicum annuum "CM334") was performed at six development stages [16, 25, 36, 38, 43, and 48 days post-anthesis (DPA)] to analyze biochemical changes. Distinct distribution patterns were observed in the changes of metabolites, gene expressions, and antioxidant activities by early (16-25 DPA), breaker (36-38 DPA), and later (43-48 DPA) stages. In the early stages, glycosides of luteolin, apigenin, and quercetin, shikimic acid, γ-aminobutyric acid (GABA), and putr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 47 publications
1
51
0
Order By: Relevance
“…However, even though considerable attention has been given to the molecular mechanism of pepper fruit development (Jang et al, 2015; Liu et al, 2017), the RGs in pepper fruit have not yet been characterized. Only a small number of the previous related studies focused on the identification of the optimal RGs for qPCR analysis under various stress conditions, or in different pepper tissues, and these studies were mainly based on the evaluation or validation of some previously reported candidate RGs (for example, house-keeping genes) under various conditions (Wan et al, 2011; Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, even though considerable attention has been given to the molecular mechanism of pepper fruit development (Jang et al, 2015; Liu et al, 2017), the RGs in pepper fruit have not yet been characterized. Only a small number of the previous related studies focused on the identification of the optimal RGs for qPCR analysis under various stress conditions, or in different pepper tissues, and these studies were mainly based on the evaluation or validation of some previously reported candidate RGs (for example, house-keeping genes) under various conditions (Wan et al, 2011; Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Values followed by different superscripts in the same column are significantly different (P<0.05). times higher, DPPH radical scavenging activities of pepper takju varieties might have been as a result of higher antioxidant potential of green peppers (Kedage et al, 2007;Sun et al, 2007;Domínguez-Martínez et al, 2014;Jang et al, 2015).…”
Section: Dpph Radical Scavenging Activities and Total Phenol Contentsmentioning
confidence: 99%
“…More than 4 times high value of total phenol contents were detected in the pepper Takju samples as compared to control. High total phenol contents of green pepper Takju were probably caused by, the addition of green peppers (Kedage et al, 2007;Sun et al, 2007;Domínguez-Martínez et al, 2014;Jang et al, 2015). Park and stated that polyphenols, flavonoids, and flavonols in Takju account for antioxidant activities.…”
Section: Dpph Radical Scavenging Activities and Total Phenol Contentsmentioning
confidence: 99%
See 2 more Smart Citations